ANGKOLA BATAK TRADITION: ISLAM, PATRILINEALITY, MODERNITY: Reviving and Challenging - Muhammad Habibi Siregar (TAWASUT, 2015)
Identity attached in a group always coincides with the perception within it. Identity of general Batak society is perceived  as the masculine  identity created the  gap  between female and male  in term of the social and economy resources. Batak society who live outside of Bonapasogit likely more solid than  they  live  in Bonapasogit.  Itcan be proved by  the  intense meeting internal Batak community more often than in Bonapasogit. Due the penetration from other cultures force them who  reside  out Bonapasogit more  united  among them. Meanwhile, for people live in Bonapasogit the only threat coming from their own community because they didn’t face the penetration from outsiders. Especially, for female Batak community the threat is the dominating patrilineality who standstill the tradition which isn’t favored to female.  In densely population in cities, marga can be used as the supported tools in relationship even many female Batak were born outside Bonapasogit  still use  marga  for their advantage purpose, especially  in bureaucracy. Meanwhile  for Angkola Batak who live their  hometown  has the  different  situation  due  don’t  get advantage  the beneficiary of marga. Because of pressure from their own community Keywords:  Islam; patrilineality; inheritance; human right; identity